2020
DOI: 10.1002/ctpp.202000067
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on high‐energy surface arc plasma excitation control of cylindrical detached shock wave

Abstract: In this study, an electrical parameter test system and a high-speed Schlieren system are used to study the control of a cylindrical detached shock wave through high-energy surface arc plasma excitation. The results show that, when plasma excitation is not applied, the bow shockwave angle around the cylinder is 52 •. After the plasma excitation is applied, the arc discharge releases a large amount of heat within a short time, generating a shockwave and a control gas bulb (CGB). As a result, the bow shockwave an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Further simulations attempted to find an optimal range of plasma power and position in terms of achievable effect, effectiveness of the method, and response time of the system to the plasma actuation. Tang et al [34] studied the evolution characteristics of high energy arc discharge actuation under a low pressure environment and used high-energy plasma actuation to effectively weaken the shock intensity of bow shock in front of a cylinder. In the incident shock wave/boundary layer interaction control, Luo et al [35] found that both 5 kHz and 10 kHz high-frequency arc discharge actuation can weaken the intensity of separated shock waves and 5 kHz actuation can suppress the low-frequency motion of separated shock waves, while 10 kHz actuation can increase the low-frequency motion energy.…”
Section: Introductionmentioning
confidence: 99%
“…Further simulations attempted to find an optimal range of plasma power and position in terms of achievable effect, effectiveness of the method, and response time of the system to the plasma actuation. Tang et al [34] studied the evolution characteristics of high energy arc discharge actuation under a low pressure environment and used high-energy plasma actuation to effectively weaken the shock intensity of bow shock in front of a cylinder. In the incident shock wave/boundary layer interaction control, Luo et al [35] found that both 5 kHz and 10 kHz high-frequency arc discharge actuation can weaken the intensity of separated shock waves and 5 kHz actuation can suppress the low-frequency motion of separated shock waves, while 10 kHz actuation can increase the low-frequency motion energy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Xie et al [ 11 ] used SparkJet actuator for the first time to achieve an effective control on Endey VI SSI over a double wedge in Mach 6.9 high‐enthalpy hypersonic flow, but the repeat frequency is only 1 Hz. Among the current active flow control methods, surface arc plasma actuation has shown excellent control effects in supersonic shock regulation, [ 12 ] shock/boundary layer interaction, [ 13,14 ] and supersonic boundary layer transition. [ 15 ] Besides, Wang et al [ 16 ] experimentally verified the control ability of the surface arc plasma actuation on Mach 6 hypersonic oblique shock over a ramp.…”
Section: Introductionmentioning
confidence: 99%